Effects of Bariatric Surgery on Cardiovascular Disease: A Concise Update of Recent Advances - Kuno, Toshiki; Tanimoto, Eriko; Morita, Sae; Shimada, Yuichi J. (Frontiers in Cardiovascular Medicine, 2019)
Patients with obesity often have multiple cardiovascular comorbidities as obesity is an established risk factor for various cardiovascular diseases (CVDs)—e. g., heart failure (HF), coronary artery disease (CAD), hypertension, dysrhythmia, and venous thromboembolism. In the United States, obesity is the nationwide public health issue of the day with the prevalence exceeding 30%. It has become a substantial health and financial burden to the society and national healthcare system; the direct cost accounted for 150 billion US dollars in 2014. Lifestyle interventions have been shown to be successful in the short term, however their long-term results are still equivocal likely due to modest weight reduction and high recurrence rates. For instance, the mean weight reduction in a randomized controlled trial of patients with type 2 diabetes mellitus (DM) and either overweight or obesity was 6.0% in the intensive lifestyle modification arm and 3.5% in the control arm. On the contrary, bariatric surgery is known to be the most effective in achieving substantial and long-term weight loss and can prevent the development of CVD risk factors such as DM, hypertension, and dyslipidemia. Bariatric surgery induces prompt weight loss within a few months which lasts for at least 12–18 months, with mean weight loss of ~35% (~70% loss of excess weight), lowering the risk of all-cause mortality, myocardial infarction, and stroke. Furthermore, recent studies demonstrated that bariatric surgery contributed to the reduction of acute care use for HF, CAD, and hypertension. On the other hand, it was reported that bariatric surgery may worsen the control of certain types of CVD (e.g., dysrhythmia), especially in the early postoperative period. Additionally, the notion that being overweight or obese could contribute to higher survival rate in certain populations (e.g., patients with HF)—also known as “obesity paradox”—has been repetitively documented in the past, while most recent investigations suggested that the observed paradox may be attributable to confounding factors including pre-existing comorbidities. Considering the aforementioned advances in the field, this paper reviews a series of recent studies with regard to the short-term and long-term effects of bariatric surgery on various types of CVDs.